2022
DOI: 10.1038/s41598-022-24428-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR improves malnutrition induced hepatic metabolic dysfunction

Abstract: Severe malnutrition accounts for half-a-million deaths annually in children under the age of five. Despite improved WHO guidelines, inpatient mortality remains high and is associated with metabolic dysfunction. Previous studies suggest a correlation between hepatic metabolic dysfunction and impaired autophagy. We aimed to determine the role of mTORC1 inhibition in a murine model of malnutrition-induced hepatic dysfunction. Wild type weanling C57/B6 mice were fed a 18 or 1% protein diet for two weeks. A third l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Previous reports suggest that PPAR-γ activation increased MMP and protected cells from apoptosis ( 95 ). Mitochondrial electron transport chain complex I and IV, COX IV content, along with ATP, are regarded as markers of mitochondrial function ( 96 , 97 ), and COX IV is a classic enzyme marker of electron transport chain ( 97 ). In the present experiment, abnormal mitochondrial morphologies, increased mitochondrial numbers, decreased mitochondrial areas, disturbed expression of Mfn2, p-Drp1 or Drp1, PGC-1α, PPAR-γ, and COX IV induced by MI or OGD, were ameliorated through MLZD administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that PPAR-γ activation increased MMP and protected cells from apoptosis ( 95 ). Mitochondrial electron transport chain complex I and IV, COX IV content, along with ATP, are regarded as markers of mitochondrial function ( 96 , 97 ), and COX IV is a classic enzyme marker of electron transport chain ( 97 ). In the present experiment, abnormal mitochondrial morphologies, increased mitochondrial numbers, decreased mitochondrial areas, disturbed expression of Mfn2, p-Drp1 or Drp1, PGC-1α, PPAR-γ, and COX IV induced by MI or OGD, were ameliorated through MLZD administration.…”
Section: Discussionmentioning
confidence: 99%
“…This was further supported by the downregulation of NTHL1 , a mitochondrial DNA glycosylase, which was downregulated due to MUN. Low PINK1 expression may be induced by mTOR signaling activity originating from upstream GF and hormone signals [ 65 ]. The notable abundance of DM hepatic genes encoding key mitochondrial metabolic enzymes ( PC , TAT , ACAD8 , PINK1 , and NTHL1 ) is a noteworthy finding that highlights the central role of mitochondria in metabolic adaptations in response to nutritional stress in the fetal liver.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to reveal whether the tryptophan-NAD + -SIRT1 and autophagy pathways are involved in the aetiology of SM-induced enteropathy and whether modulating these pathways can protect intestinal structure and function. Using mouse and organoid models of malnutrition induced enteropathy, 22 , 23 we discovered that low plasma tryptophan was associated with a reduction in SIRT1 mediated mitochondrial biogenesis and autophagy activity. We demonstrated the therapeutic potential of NAM in ameliorating malnutrition enteropathy and showed that regenerating NAD + through the NAD + -salvage pathway with NAM supplementation improved autophagy, intestinal barrier function, and mitochondrial damage.…”
Section: Introductionmentioning
confidence: 99%